Failure analysis of general stator and uniform wall thickness stator. (December 2018) - Shi, Changshuai; Zhu, Xiaohua; Chen, Yike; Tang, Liping
Abstract: Stator lining of positive displacement motor (PDM) is prone to generate thermal fatigue failure because of viscoelastic hysteresis of the rubber material. Based on the thermo-mechanical coupling modeling and rubber material testing, finite element method was used to study the effect of environment temperature and thermo-viscoelastic hysteresis to the lining thermal failure of general stator and uniform wall thickness stator. The results show that the deformation and temperature field of general rubber lining has been less affected by the environment temperature than thermo-viscoelastic hysteresis whose distribution of temperature field appears oval-shaped and the temperature gradient is large. Stator lining's temperature increases with the increasing of motor interference and well depth, and the rubber lining's thermal failure modes observed in practice are consistent with the calculation results. The temperature field distribution of uniform wall thickness rubber lining is relatively uniform, and the highest temperature and temperature rise are less affected by the motor interference and well depth, especially with small motor interference and in the shallow well. Therefore, the uniform wall thickness rubber lining has very obvious advantages in prolonging service life and improving the work performance of PDM. Highlights: Maximum deformation of general stator rubber lining occurs at the top of the lining. Deformation curve of general rubber lining inner wall indicates a sinusoidal periodic changes. Highest temperature is at the centre of the rubber lining's thickest section. Thermal failure occurred in the thickest section of the lining, which is consistent with observations in practice. The temperature field and deformation of uniform wall thickness rubber lining is more uniform.